2015
DOI: 10.5194/tc-9-1203-2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the firn structure of the western Greenland Ice Sheet caused by recent warming

Abstract: Abstract. Atmospheric warming over the Greenland Ice Sheet during the last 2 decades has increased the amount of surface meltwater production, resulting in the migration of melt and percolation regimes to higher altitudes and an increase in the amount of ice content from refrozen meltwater found in the firn above the superimposed ice zone. Here we present field and airborne radar observations of buried ice layers within the near-surface (0-20 m) firn in western Greenland, obtained from campaigns between 1998 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 33 publications
7
68
0
1
Order By: Relevance
“…A key uncertainty in the mass budget is the degree of meltwater retention due to refreezing and capillary forces (e.g., Janssens and Huybrechts, 2000;Harper et al, 2012;Vernon et al, 2013;van As et al, 2016). As the climate has warmed, the zone where melt and rainfall occurs over the snowpack has expanded to higher elevations in the last decade (Howat et al, 2013;de la Peña et al, 2015). Observations from Polashenski et al (2014) confirm that firn warming is a both long-term (>50 years) and widespread effect.…”
Section: Introductionmentioning
confidence: 51%
“…A key uncertainty in the mass budget is the degree of meltwater retention due to refreezing and capillary forces (e.g., Janssens and Huybrechts, 2000;Harper et al, 2012;Vernon et al, 2013;van As et al, 2016). As the climate has warmed, the zone where melt and rainfall occurs over the snowpack has expanded to higher elevations in the last decade (Howat et al, 2013;de la Peña et al, 2015). Observations from Polashenski et al (2014) confirm that firn warming is a both long-term (>50 years) and widespread effect.…”
Section: Introductionmentioning
confidence: 51%
“…These changes are highly significant considering that typical values for total firn air content in the dry snow zone range between 20 and 25 m . Recent research has shown that warm summers can generate thick ice layers that prevent meltwater from reaching the deeper pores, further reducing the meltwater buffering capacity (De la Peña et al, 2015;Machguth et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved through statistical/dynamical downscaling in combination with targeted in situ observations. Examples of important processes that are poorly or not at all represented in current models are interactive snow/ice darkening by future enhanced dust/black carbon deposition or microbiological processes (Stibal et al, 2012), and sub-, supra-and englacial hydrology, including vertical and horizontal flow of meltwater in firn or over ice lenses (De la Peña et al, 2015;Machguth et al, 2016). Other emerging research topics of GrIS melt climate are the impact of atmospheric circulation changes on Greenland melt (Hanna et al, 2013a(Hanna et al, , 2014McLeod and Mote, 2016;Tedesco et al, 2013), the impact of rain on ice sheet motion (Doyle et al, 2015), the effect of liquid water clouds on the surface energy balance and melt (Bennartz et al, 2013;Van Tricht et al, 2016) and the increased role of turbulent heat exchange during strong melting episodes over the margins of the GrIS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water may flow laterally over ice layers or crusts, which reduces travel times in catchments and has a significant impact on catchment-scale hydrology; alternatively, preferential flow in snow may promote vertical percolation instead (Eiriksson et al, 2013). Recent studies have demonstrated that the increased melt on the Greenland Ice Sheet during the last few decades led to changes in the firn structure, particularly through the formation of ice layers by percolating water in sub-freezing snow (de la Peña et al, 2015). These ice layers can reach considerable vertical extents on the order of 1 m (Machguth et al, 2016) and may reduce the storage capacity of meltwater in the firn by making access to deeper firn layers more difficult.…”
Section: Introductionmentioning
confidence: 99%